Multiple Dosing of Ephedra‐Free Dietary Supplements: Hemodynamic, Electrocardiographic, and Bacterial Contamination Effects. Issue 3 (11th December 2012) - Foster, L; Allan, M C; Khan, A; Moore, P; Williams, D K; Hubbard, M; Dixon, L; Gurley, B J
<x xml:space="preserve">Abstract</x> Four popular ephedra‐free dietary supplements were evaluated for their effects on heart rate (HR), blood pressure (BP), and electrocardiographic (ECG) parameters. Twelve healthy men participated in a study randomized for product sequence, with a 21‐day washout period between supplement‐administration phases. Throughout the study, Holter monitors were used to assess ECG and HR activity. BP was assessed automatically on multiple occasions. The supplements were ingested three times daily for 3 days. Caffeine content, microbial load, and serum caffeine concentrations were determined. Mean systolic (SBP) and diastolic BP (DBP) readings showed significant increases relative to baseline (10.8 ± 2.5 and 5.3 ± 3.1 mm Hg, respectively; P < 0.05). All supplements significantly increased HR and decreased bradycardia runs; abnormal atrial/ventricular events were frequently noted. Gastrointestinal and sympathomimetic symptoms were also common. Two supplements were heavily contaminated with Bacillus species. In light of these findings, the use of ephedra‐free dietary supplements should be discouraged in individuals with hypertension, diabetes, or other cardiovascular diseases. Clinical Pharmacology & Therapeutics (2013); 93 3, 267–274. doi:10.1038/clpt.2012.241